1979
DOI: 10.1111/j.1440-1827.1979.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Thymus and Peripheral Lymphoid Tissues in Fatal Measles

Abstract: As a result of re-examining 14 autopsy cases of fatal,,measles, neither aplastic nor hypoplastic thymuses were found even in a case with giant cell pneumonia, but there were degenerative and/or necrotic changes with giant cells mostly in the thymus and less in the peripheral lymphoid organs such as spleen, lymph nodes, Peyer's patches and tonsils. This damage of the lymphoid system was associated with the occurrence of complications, particularly of giant cell pneumonia and encephalitis. The lymphoid cell dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…MV initially replicates in the respiratory tracts and then spreads to the local lymphoid tissue. This second viremia allows the spreading of the virus to other lymphoid organs, including the thymus, where a profound thymic injury, characterized by degenerative and/or necrotic lesions, occurs (8,62). Human thymic stromal cells, particularly TEC, have been described as targets for MV during the acute phase of infection (35,64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MV initially replicates in the respiratory tracts and then spreads to the local lymphoid tissue. This second viremia allows the spreading of the virus to other lymphoid organs, including the thymus, where a profound thymic injury, characterized by degenerative and/or necrotic lesions, occurs (8,62). Human thymic stromal cells, particularly TEC, have been described as targets for MV during the acute phase of infection (35,64).…”
Section: Discussionmentioning
confidence: 99%
“…Growth arrest has also been noted upon interaction of MV-H and-F proteins with uninfected cells (20,49,52), strongly suggesting that MV viral proteins share the ability to inhibit cell proliferation through unidentified cellular receptors. MV replication is responsible for thymic involution (8,62). However, thymic epithelium disruption could also be responsible for extracellular release of N after apoptosis of MV-infected TEC.…”
Section: Discussionmentioning
confidence: 99%
“…Measles virus infects epithelial cells and monocytes in the thymus (25,45), leading to a decrease in the size of the thymic cortex (10,44). Measles virus replication in human thymic epithelial cells in vitro results in terminal differentiation and apoptosis (39).…”
mentioning
confidence: 99%
“…Autopsies of patients with fatal measles infections demonstrated degenerative and/or necrotic lesions in the thymus associated with a rapid and predominant loss of the thymic cortex (38). A marked involution of the thymic medulla was also observed, and MV antigens were found in Hassal's corpuscules (11,38). We previously demonstrated that, in vitro, MV replication profoundly affects human cortical TEC biology (37).…”
mentioning
confidence: 92%
“…MV initially replicates in the respiratory tract and then spreads to local lymphoid tissue, where virus replication can occur in macrophages and/or dendritic cells. This secondary viremia allows the spreading of the virus to other lymphoid organs, including the thymus (11,27,38). Autopsies of patients with fatal measles infections demonstrated degenerative and/or necrotic lesions in the thymus associated with a rapid and predominant loss of the thymic cortex (38).…”
mentioning
confidence: 99%